2017
DOI: 10.1080/00905992.2016.1258048
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and cultural considerations in constructing European identity among ethnic minority groups in Lithuania in a generational perspective

Abstract: Research on European identity focuses mainly on majority populations in Western European countries without differentiating among specific population groups and generations, and, above all, disregarding ethnic minority groups living in Central and Eastern Europe. This paper addresses this gap by investigating the development of European identity among three ethnic minority groups in Lithuania: Belarusians, Poles, and Russians. Theoretically, the project is based on the instrumental approach, which argues that E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…From another side, they strongly associate negative consequences with the EU membership: social, economic, and ecologic problems. This finding is consistent with the previous research in Lithuania which has shown that perceived threats to their country due to EU membership do not allow the minority of Russians to identify with Europe or the EU ( Waechter, 2017 ). In turn, cultural considerations are particularly important for construction of ethnic identity.…”
Section: Discussionsupporting
confidence: 92%
“…From another side, they strongly associate negative consequences with the EU membership: social, economic, and ecologic problems. This finding is consistent with the previous research in Lithuania which has shown that perceived threats to their country due to EU membership do not allow the minority of Russians to identify with Europe or the EU ( Waechter, 2017 ). In turn, cultural considerations are particularly important for construction of ethnic identity.…”
Section: Discussionsupporting
confidence: 92%
“…As concerns affective European identity, young people from new Member States are even more affective than their peers from old Member States. Waechter (2017) links the generational effect to the numerous opportunities that the EU provides for young people regarding travelling, studying and working abroad.…”
Section: Demographicsmentioning
confidence: 99%
“…It might make a difference if PMB share their religious identity with the majority group members they have contact with. Also identification with superordinate entities may play a role, for example identification with Europe or the European Union (e.g., Teney, Hanquinet, & B€ urkin, 2016;Waechter, 2017). Therefore, future studies may also differentiate between positive and negative contact with majority group members having the same or a different religious affiliation.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Second, other forms of identification beyond identification with the majority, minority, and religious group may function as mediators, for example identification with the inhabitants of a city, region, or neighborhood PMB live in (e.g., Fleischmann & Phalet, 2016). Also identification with superordinate entities may play a role, for example identification with Europe or the European Union (e.g., Teney, Hanquinet, & B€ urkin, 2016;Waechter, 2017). And third, future research may examine other outcome variables (or the effects of acculturation attitudes on further outcome variables), like health, employability, or psychological and sociocultural adaptation of PMB.…”
Section: Limitations and Future Researchmentioning
confidence: 99%